2014
DOI: 10.3402/ijch.v73.24324
|View full text |Cite
|
Sign up to set email alerts
|

Household reporting of childhood respiratory health and air pollution in rural Alaska Native communities

Abstract: BackgroundAir pollution is an important contributor to respiratory disease in children.ObjectiveTo examine associations between household reporting of childhood respiratory conditions and household characteristics related to air pollution in Alaska Native communities.DesignIn-home surveys were administered in 2 rural regions of Alaska. The 12-month prevalence of respiratory conditions was summarized by region and age. Odds ratios (ORs) were calculated to describe associations between respiratory health and hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Paraffin, together with electricity, is the most common source of energy in informal settlement communities in South Africa, as well as in many other low‐ and middle‐income countries, among communities of low socioeconomic status . The level, duration, and time pattern of exposure in microenvironments determine the extent of personal exposure to pollutants from sources such as paraffin, since children spend considerable proportion of their time indoors . This is consistent with other studies that estimated indoor air pollution from biomass fuel use including paraffin.…”
Section: Discussionsupporting
confidence: 84%
“…Paraffin, together with electricity, is the most common source of energy in informal settlement communities in South Africa, as well as in many other low‐ and middle‐income countries, among communities of low socioeconomic status . The level, duration, and time pattern of exposure in microenvironments determine the extent of personal exposure to pollutants from sources such as paraffin, since children spend considerable proportion of their time indoors . This is consistent with other studies that estimated indoor air pollution from biomass fuel use including paraffin.…”
Section: Discussionsupporting
confidence: 84%
“…Exposure to wood smoke has been identified as a risk factor of asthma in Chinese rural communities and some underdeveloped regions where using wood for cooking is very prevalent [15,30,31]. However, a multivariate analysis of Indian adults revealed that cooking fuel type (clean or unclean) was not an independent factor associated with asthma [29].…”
Section: Discussionmentioning
confidence: 99%
“…Air quality has been identified as a risk factor for childhood pneumonia and mortality in low- and middle-income countries [30]. In the United States, levels of ambient air pollutants have been associated with death rates from pneumonia [31] and air pollution has been linked to childhood respiratory health in rural Alaska Native communities [32]. However, much of the literature has focused on childhood illness and also has not specifically examined the impact of air quality on hospitalization rates.…”
Section: Discussionmentioning
confidence: 99%